Design and synthesis of 2-oxindole based multi-targeted inhibitors of PDK1/Akt signaling pathway for the treatment of glioblastoma multiforme - Sestito, S.; Nesi, G.; Daniele, S.; Martelli, A.; Digiacomo, M.; Borghini, A.; Pietra, D.; Calderone, V.; Lapucci, A.; Falasca, Marco; Parrella, P.; Notarangelo, A.; et al. (2015)
© 2015 Elsevier Masson SAS. Aggressive behavior and diffuse infiltrative growth are the main features of Glioblastoma multiforme (GBM), together with the high degree of resistance and recurrence. Evidence indicate that GBM-derived stem cells (GSCs), endowed with unlimited proliferative potential, play a critical role in tumor development and maintenance. Among the many signaling pathways involved in maintaining GSC stemness, tumorigenic potential, and anti-apoptotic properties, the PDK1/Akt pathway is a challenging target to develop new potential agents able to affect GBM resistance to chemotherapy. In an effort to find new PDK1/Akt inhibitors, we rationally designed and synthesized a small family of 2-oxindole derivatives. Among them, compound 3 inhibited PDK1 kinase and downstream effectors such as CHK1, GS3Ka and GS3Kß, which contribute to GCS survival. Compound 3 appeared to be a good tool for studying the role of the PDK1/Akt pathway in GCS self-renewal and tumorigenicity, and might represent the starting point for the development of more potent and focused multi-target therapies for GBM.